INFLUENCE OF PRODUCT QUALITY, BRAND IMAGE AND PRICE CONCERNING AUTOMOBILE BUYING DECISION OF TOYOTA AVANZA AT PT. NASMOCO MAJAPAHIT SEMARANG - Putra, Arya Willis Nugraha; Waluyo, Handoyo Djoko; Nugraha, Hari Susanta (Jurnal Ilmu Administrasi Bisnis, 2015)
This research was based on rapid automotive sector business development, especially automobile. Specifically, this research was discuss about automobile buying of Toyota Avanza brand at PT Nasmoco Majapahit Semarang during 2011 - 2014 keep have sale descending and it's sale target. If that case wasn't improve and solve, probably will presence problem for PT. Nasmoco Majapahit Semarang next.Aim of this research was to found product quality, brand image and price concerning automobile buying decision of Toyota Avanza Semarang. This research type was explanatory, with data collection technique by questionaire and interview. Sampling collection technique by non probability sampling method was using purposive sampling. The sample was about 100 persons as consumers who use and bought Toyota Avanza automobile on PT Nasmoco Majapahit Semarang. This research was using qualitative and quantitative analisys techniques. Quantitative analysisÂ  was using validity, correlation, both simple and double linear regression analysis, determination coefficient, signification test ( t and f test), using SPSS tools.The results showed that the quality of the product (X1) , brand image (X2) and price (X3) simultaneously influence consumer purchasing decisions ( Y ) . Based on the results of a two-stage regression , variables that have the most dominant effect is the brand image (X1) .Conclusion obtained was between product quality and price was have significant influence concerning buying decision. Suggestion give was automobile of Toyota Avanza brand at least take inovation quickly and accordance with consumer desirabilities and for PT Nasmoco Majapahit Semarang was often implemented promotion by giving quite big discount for it's product.